(untitled) (Global Journal of Science Frontier Research, 2012)
To verify the pollen rain in offshore locations where there is no vegetation, two shallow sites – approximately 15km (20m water depth) and 43 km (61m water depth) – offshore eastern Niger Delta were aeropalynologically sampled and studied. Improvised pollen sampler made of a cylindrical tin of 5cm diameter was used with diluted formalin solution as the medium and sited on a stationary vessel. Collected samples were subjected to acetolysis and recovered palynomorphs studied microscopically. Eight pollen genera were recovered from the proximal site while five genera were found in the distal site. Pollen population is higher in the proximal than distal sites. Large sized pollen of Sida sp. is seven times higher in number in the proximal than the distal sites. Fungal species - cf. Alternaria and cf. Cladosporium - spores and hyphea as well as mycelia of other fungi were recovered along with charred Gramineae cuticles. This scenario of pollen settling from the air is similar to that from water currents. The proximal area has higher proportions and the larger ones settle first. The study confirms pollen rain as important contributor to marine sediments in the Niger Delta with implications for paleoclimatology, palynostratigraphy and allergy sensitivity.